ANALYSIS OF FINANCIAL PERFORMANCE OF CERAMIC, PORCELAIN, AND GLASS SUB-SECTOR INDUSTRIES - Kevin Adhiya Kurniawandi (Accounting Study Program, Universitas Ciputra Surabaya, 2021)
One of basic industrial and chemical companies listed on the Indonesia Stock Exchange (IDX is the ceramic, porcelain and glass sub-sector industry. The large number of imported ceramics from China and India has resulted in intense competition between local and imported products. This is also marked by the existence of a government regulation to reduce the number of imported products in Indonesia by increasing 10% tax on imported ceramics. The intense competition can result local products being unable to compete with imported products. The purpose of this study was to determine the direct effect of the liquidity ratio, solvency ratio, dan activity ratio on Return On Assets (ROA) and Market to Book Value (MBV). The samples used in this study were 48 companies form the ceramic, glass, and porcelain sub-sector cluster listed on the Indonesia Stock Exchange (IDX). Data Collection uses secondary data from the company’s financial statements. Data analysis used multiple linear regression using SPSS 22. The results of this study indicate that the current ratio and total asset turnover have positive effect on Return On Assets (ROA). Meanwhile the debt to equity ratio, cash turnover, account receivable turnover, and inventory turnover had no effect on Return On Assets (ROA). Total asset turnover and cash turnover have positive effect on Market to Book Value (MBV). Meanwhile, current ratio, debt to equity ratio, account receivable turnover and inventory turnover have no effect on Market to Book Value (MBV).